Optimisation des modèles de perte dans un canal physique pour la communication mobiles - الزايز, عربية (university of Eloued جامعة الوادي, 2019)
In mobile radio systems, path loss models are necessary for proper planning, interference estimations, frequencies assignments and cell parameters which are basic for network planning process. Empirical models are the most adjustable models that can be suited to different types of environments. The measured path loss is compared with theoretical path loss estimated by the most widely empirical models «Cost231», «Hata», «SUI» and «Egli». The best model to estimate the measured path loss is optimized using genetic algorithm to predict path loss for suburban and rural area. The RMSE and the other test criteria between measured and estimated data are calculated for various path loss models. It turned out that the adjusted " COST 231" model outperforms the other studied models. The investigated results can help telecommunication engineers improve their planning and design of microcellular system. تعتبر نماذج فقدان المسار لدى الأنظمة الخلوية عنصرا ضروريا لأجل التخطيط السليم، وذلك من أجل تقدير التداخلات ومن أجل تعيين الترددات ومختلف اعدادات الخلية والتي تعتبر ضرورية لعملية تخطيط الشبكات. كما تعد النماذج التجريبية النماذج الاكثر قابلية للتعديل حيث يمكنها ان تكون مناسبة للعديد من البيئات . في اطار هذا العمل تمت مقارنة قيم فقدان المسار المقاسة والمقدرة حسب النماذج التجريبية التالية «Cost231» , «Hata», «SUI» «Egli» ، كما تم اختيار وتحسين النموذج ذو الافضل نتائج باستعمال الخوارزمية الجينية . وكل هذا يتم حسب معيار تقييم الخطأ RMSE وخواص اخرى مطبقة على كل من المعطيات الحقيقة المقاسة والقيم المقدرة حسب النموذج. يعتبر النموذج " COST 231 " المعدل الافضل من بين النماذج المدروسة المتبقية. إن النتائج المحصل عليها من هذه الدراسة تساعد مهندسي الاتصالات على تحسين عمليتيَ تخطيط وتصميم أنظمتهم الميكرو خلوية.
مذكرة ماستر تخصص في انظمة الاتصالات
Keywords: GSM, path loss, empirical models, genetic algorithm.; GSM ، فقدان المسار، النماذج التجريبية، الخوارزمية الجينية